Pendampingan Audit Mutu Perusahaan (ISO 9001) - Rustam, Akie Rusaktiva; Widiastutik, Rika Nur (Jurnal ABM Mengabdi, 2024)
This activity aims to analyze the effectiveness of implementing the ISO 9001 certification audit process in service companies. Objective, systematic and independent inspections and assessments are useful for knowing that quality audit activities, related results are in accordance with planned arrangements, various regulations have been implemented effectively, and are in accordance with commitments, policies, goals and quality targets that have been planned or determined. By carrying out regular and planned quality audits, non-conformities and potential non-conformities in the quality system can be detected, so that appropriate corrective and preventive actions can be taken. This community service activity succeeded in implementing and providing assistance to PT BMA regarding the ISO 9001:2015 audit. This activity also succeeded in finding improvements related to the PT BMA auditor's report and also succeeded in providing recommendations for improvements related to the results of post-ISO 9001:2015 Audit assistance. The implication of this activity is that it is able to encourage PT BMA to carry out an ISO 9001:2015 audit because it already has preparations through assistance with the ISO 9001:2015 audit which has been carried out by the service team